Sentimen Analisis Publik Terhadap Joko Widodo terhadap wabah Covid-19 menggunakan Metode Machine Learning - Hikmawan, Sisferi; Pardamean, Amsal; Khasanah, Siti Nur (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2020)
Abstract Analyzing public sentiment towards a government policy is no longer impossible, the process of analyzing with data mining is a method that is often used. The Data Mining method is always related to the dataset, with the keywords